The Impact of Instability of Gossip’s Meaning to The characterizations in Julia Quinn’s Bridgerton: The Duke and I Novel: A Derridean Deconstruction Perspectives - Rusdianti, Alisya (Balai Bahasa Provinsi Jawa Timur, 2023)
This research explored characterizations instabilities towards impacts of gossip in Julia Quinn’s Bridgerton: The Duke and I novel. The impacts of gossip portrayed significantly towards the characterization of the main characters and the society in the novel. The gossip, for instance became contemplating materials, livelihood, and entertainment in the society, thus the characterizations in the novel became unstable and dinamic due to the attachment between gossip and society. This researh applied Derrida’s Deconstruction as theory and method. The results of this research indicated the impact of gossips to the characterization in the novel resemblanced the undecidability of text. The text is independent and fluid, thus the impact of text characteristics could be represented by the undecidablity of characterization—based on the conflict embedded to the characters. Thus, the conclusions in this research show that the meaning of gossip in the novel is undecidable and the characterization continues to move and develop as the conflict in the novel develops which is caused by the movement of the meaning of gossip.